053 The characteristics of emergency attendees for epilepsy in London hospitals. Issue 3 (9th February 2012) - Noble, A; Goldstein, L H; Seed, P; McCrone, P; Morgan, M; Ridsdale, L
Abstract : Introduction: People with epilepsy frequently attend emergency departments and are admitted. Reducing unplanned hospitalisations is a health service target. Little information is, however, available on this group. Objectives: Describe the characteristics of those attending for epilepsy and the factors associated with increased use. Methods: We prospectively recruited 85 patients attending three London emergency departments for seizures (diagnosed for ≥1 year). Patients completed questionnaires on service use and psychosocial state. Results: Mean age was 41 and 53% male. 58% had focal onset epilepsy, 20% generalised epilepsy, the predominant seizure type being generalised or secondary generalised. None had been seizure free in the prior year. The mean (3.2) and median number (2) of emergency attendances in the prior year exceeded that of the general population and for those with other chronic conditions. They had poorer quality of life, psychological wellbeing, epilepsy knowledge and greater perceived stigma than the wider epilepsy population. Most received epilepsy care in line with guidelines. In regression, knowledge, stigma, medication management, and seizure frequency (in descending order) predicted use. Conclusions: People presenting to emergency departments due to epilepsy reattend more frequently than people with other chronic conditions. Interventions aiming to reduce attendances need to consider the frequent seizures, stigma and suboptimal self-management reported by patients.